Thermal Comfort Properties On Army Uniform With Objective And Subjective Evaluation - Jamil, Ilya Fildzah Zamelia; Abu Bakar, Bachik (Progress in Engineering Application and Technology, 2021)
This study was aimed to conduct an evaluation on the army uniform thermal comfort properties objective and subjectively. The type fabric used for the test is poly cotton which is a blend fabric of natural cotton fibers and synthetic polyester fibers. The procedure of the testing is in compliance with (American Society for Testing and Materials) ASTM Standards. The assessments included two types of physical tests to study the comfort properties of the uniform. They are water vapor transmission and thermal insulation. As to test the properties subjectively, the wear trial test is conducted and a questionnaire was distributed. It is to gain a better view of the comfort level offered by the clothing. The overall results would help to determine if the army uniform has an excellent thermal comfort properties for the wearer.